Diaspora mobilization and the Ukraine crisis: old traumas and new strategies. Issue 11 (18th August 2019) - Nikolko, Milana
ABSTRACT: This article presents an analysis of mobilization strategies among Ukrainian diaspora groups in Canada in their response to the Ukrainian crisis of 2014–15. By mapping recent Ukrainian diaspora activism, the purpose of this article is to understand international non-state actor influence on transitional justice during crisis. The first part draws on studies of traumatic memories and the role they play in developing a victim-based identity among a diaspora. Practices of memorialization of the famine 1932–33 in Ukraine were created through emotional causal mechanisms that captured traumatic emotions on paper in the diaspora, creating narratives that were further sustained through value-based mechanisms. The second part explains how the diaspora bridged its interpretation of traumatic memories with the home country. The last part demonstrates how existing narratives and discourses were utilized through a strategic causal mechanism to create a rapid response among Ukrainian Canadians to the crisis in Ukraine.